Nilai Pendidikan Profetik dalam Filantropi Masyarakat Grenden Jember - Miftakhuddin (Nusa Putra University, 2021)
To date, traditional philanthropy has not been widely studied in the perspective of educational sciences. In fact, traditional philanthropy has the potential to be a reference for character education based on local wisdom. This study aims to interpret educational values in the traditional philanthropy of the Grenden society. Using an ethnographic design conducted throughout 2018-2020, this study succeeded in revealing a number of educational values from the philanthropic activities of the class of farmers, limestone miners, and fishermen. Further analysis reveals that the philosophical foundation and practical guidelines of philanthropy are based on the understanding of the Javanese Islam. The findings of this study contribute to the development of educational science, especially character education. This research offers a solution to the problem of character education that has been carried out by showing a role model first. Therefore, the implications of this research are in the form of criticism and correction of the implementation of character education that is not based on the values of local wisdom. Included in the object of this research criticism are the basics of character education offered by Thomas Lickona, and instead this research promotes the value of character education based on the wisdom of the Indonesian people as echoed by Ki Hadjar Dewantara.